2018
DOI: 10.1159/000488736
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Activation Induced by Sirt1 Ameliorates Acute Lung Injury After Intestinal Ischemia/Reperfusion Through NOX4-Mediated Gene Regulation

Abstract: Background/Aims: Nuclear erythroid 2-related factor-2 (Nrf2) is a major stress-response transcription factor that has been implicated in regulating ischemic angiogenesis. We investigated the effects of Nrf2 in regulating revascularization and modulating acute lung injury. Methods: The expression of Nrf2 and sirtuin1 (Sirt1) was assessed in lung tissue by western blotting and immunofluorescence staining after intestinal ischemia/reperfusion (IIR) in Nrf2–/– and wild-type (WT) mice. The involvement of Nrf2 in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…The mitochondria observed via transmission electron microscopy had shrunk in size, the cristae had decreased or disappeared, and the outer membrane had ruptured in the Nrf2 -/- IIR group, suggesting that Nrf2 can alleviate ferroptosis ( Figure 2D ). Similarly, the extent of pathological damage in the Nrf2 -/- IIR group was more severe than that observed in WT mice ( Figure 2E ), suggesting that Nrf2 plays a protective role in ALI, which is also consistent with previous studies [ 17 ]. The damage observed in the IIR + Fe group was more severe than that of the corresponding group of WT mice, and the damage in the Nrf2 knockout mice was also reduced following the administration of Fer-1 ( Figure 2E ).…”
Section: Resultssupporting
confidence: 91%
“…The mitochondria observed via transmission electron microscopy had shrunk in size, the cristae had decreased or disappeared, and the outer membrane had ruptured in the Nrf2 -/- IIR group, suggesting that Nrf2 can alleviate ferroptosis ( Figure 2D ). Similarly, the extent of pathological damage in the Nrf2 -/- IIR group was more severe than that observed in WT mice ( Figure 2E ), suggesting that Nrf2 plays a protective role in ALI, which is also consistent with previous studies [ 17 ]. The damage observed in the IIR + Fe group was more severe than that of the corresponding group of WT mice, and the damage in the Nrf2 knockout mice was also reduced following the administration of Fer-1 ( Figure 2E ).…”
Section: Resultssupporting
confidence: 91%
“…Upregulation of SIRT1 expressions, in turn, increases expression levels of Nrf2 and phase 2 antioxidant enzymes, while silencing SIRT1 with siRNA decreases Nrf2 protein as well as activity of ARE promotor [182]. Moreover, upregulation and activation of Nrf2 expression by SIRT1 were also observed [183]. e second mechanism comprises direct upregulation of Nrf2 expression because studies have shown that resveratrol increases Nrf2 expression in kidney, heart, and lung tissues [184,185].…”
Section: Protection From Uv Irradiation and Antioxidant Defensementioning
confidence: 99%
“…Importantly, many effects of SIRT1 that are relevant to the suppression or avoidance of inflammation have been also observed upon treatment with melatonin (Figure ). In addition to the inhibition of NF‐κB activation, to Nrf2 upregulation, and to the avoidance of NLRP3 inflammasome activation, several further anti‐inflammatory actions of SIRT1 have become known. This concerns, for example, an inhibition of TLR4, which was demonstrated in renal collecting duct cells by either SIRT1 overexpression or activation by SRT1720, effects that were blocked by Sirt1 siRNA or the sirtuin inhibitors sirtinol and EX527 .…”
Section: Downstream Factors Of Melatonin's Actions With Relevance To mentioning
confidence: 99%